(untitled) (Journal of Forensic Medicine & Toxicology, 2011)
Imaging techniques are a powerful tool in forensic sciences. Radiology has been used extensively in conventional dental identification, anatomically based identification and identification using maxillofacial skeletal landmarks such as the frontal sinus. Oral and maxillofacial radiographs provides one of the best avenues for forensic identification of human remains, because teeth, unlike other body parts, are highly resistant to decomposition and are not easily destroyed. Post mortem (PM) dental information is compared with ante mortem (AM) information in an attempt to establish the identity of the remains. Dental information typically includes x ray-based radiographs—including periapical film and bitewing radiographs, and panoramic radiographs. The aim of this review is to cover the various uses of oral and maxillofacial radiography in the emergent field of forensic sciences.